Risk factors for, and prevention of, shoulder injuries in overhead sports: a systematic review with best-evidence synthesis - Martin Asker; Hannah L. Brooke; Markus Waldén; Ulrika Tranæus; Fredrik Johansson; Eva Skillgate; Lena W. Holm (2018)
Objective To assess the evidence for risk factors and prevention measures for shoulder injuries in overhead sports. Design Systematic review with best-evidence synthesis. Data sources Medline (Ovid), PubMed (complementary search), Embase (Elsevier), Cochrane (Wiley), SPORTDiscus (Ebsco) and Web of Science Core Collection (Thomson Reuters), from 1 January 1990 to 15 May 2017. Eligibility criteria for selecting studies Randomised controlled trials, cohort studies and case-control studies on risk factors or prevention measures for shoulder injuries in overhead sports. The eligible studies were quality assessed using the Scottish Intercollegiate Guidelines Network criteria. Results Of 4778 studies identified, 38 were eligible for quality review and 17 met the quality criteria to be included in the evidence synthesis. One additional quality study presented a shoulder injury prevention programme. Most studies focused on baseball, lacrosse or volleyball (n=13). The risk factors examined included participation level (competition vs training) (n=10), sex (n=4), biomechanics (n=2) and external workload (n=2). The evidence for all risk factors was limited or conflicting. The effect of the prevention programme within the subgroup of uninjured players at baseline was modest and possibly lacked statistical power. Conclusions All investigated potential risk factors for shoulder injury in overhead sports had limited evidence, and most were non-modifiable (eg, sex). There is also limited evidence for the effect of shoulder injury prevention measures in overhead sports. PROSPERO trial registration number CRD42015026850 .